Comparison of efficacy of CT scan and ultrasound in patients with blunt abdominal trauma - Ravindernath, M. L.; Reddy, G. Mahender (International Journal of Advances in Medicine, 2017)
Background: Trauma has become one of the most common cause of hospitalization. The main reason for imaging and screening the patients is to identify the life-threatening injuries as soon as possible so that appropriate treatment can be given immediately. In the past few years, both USG and CT have been widely used to detect the abdominal trauma and have replaced the older methods. This study was undertaken to compare the efficacy of CT scans and Ultrasound in the patients with blunt abdominal trauma. Methods: Patients who had come to our hospital with blunt abdominal trauma and who were stable enough to undergo both USG and CT scans were included into the study. Apart from routine tests, both USG and CT scans were performed for all the patients. Results: The most common cause of trauma was road or vehicular accidents (58.9%) followed by fall from heights (32.1%). Of the organs which were affected, the most one was liver (73.2%), followed by spleen (51.8%), 46.4% of kidneys and 12.5% of the pancreas. Hemoperitoneum was identified in all the 56 patients with CT scan while the same was identified only in 47 cases (83.9%) with USG. Conclusions: CT scan is a superior diagnostic tool for the detection of Blunt abdominal trauma compared to USG. However, the patient needs to be hemodynamically stable for CT to be performed.